2019
DOI: 10.1111/1471-0528.15886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of QUiPP prediction algorithm on treatment decisions in women with a previous preterm birth: a prospective cohort study

Abstract: Objective The QUiPP algorithm combines cervical length, quantitative fetal fibronectin (qfFN) and medical history to quantify risk of preterm birth. We assessed the utility of QUiPP to inform preterm birth prevention treatment decisions. Design A prospective cohort study with a subsequent impact assessment using the QUiPP risk of birth before 34 weeks’ gestation. Setting A UK tertiary referral hospital. Sample In all, 119 women with previous spontaneous preterm birth (sPTB) or preterm premature rupture of memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Two studies compared and combined fFN with CL as a predictor of a PTB in asymptomatic women, and both found fFN to be a superior test [85][86][87]. However, others have demonstrated that fFN results alone are not useful [88][89][90]. In a systematic review [91] of six randomized trials in which a total of 546 women with threatened preterm labor were randomly assigned to management with reported or concealed fFN results, clinician knowledge of their fFN results did not reduce the rates of maternal hospitalization or a PTB at <34 weeks of gestation.…”
Section: Fetal Fibronectin (Ffn)mentioning
confidence: 99%
“…Two studies compared and combined fFN with CL as a predictor of a PTB in asymptomatic women, and both found fFN to be a superior test [85][86][87]. However, others have demonstrated that fFN results alone are not useful [88][89][90]. In a systematic review [91] of six randomized trials in which a total of 546 women with threatened preterm labor were randomly assigned to management with reported or concealed fFN results, clinician knowledge of their fFN results did not reduce the rates of maternal hospitalization or a PTB at <34 weeks of gestation.…”
Section: Fetal Fibronectin (Ffn)mentioning
confidence: 99%
“…Of the 16 studies that included model development, five studies collected data prospectively (Allouche et al, 2011; Gioan et al, 2018; Mercer et al, 1996; Misra et al, 2001; Zhu et al, 2017), 10 studies collected data retrospectively (Baer et al, 2018; de Caunes et al, 1990; Goyal et al, 2015; Hueston, 1998; Lee et al, 2020; Luo et al, 2016; Morken et al, 2014; Tan et al, 2007; Weber et al, 2018; Woolery, 1992), and one study combined prospective and retrospective designs (Takagi et al, 2012). Of the five studies that only conducted validation, three studies collected data prospectively (R. K. Creasy et al, 1980; Goodfellow et al, 2019; Holbrook et al, 1989), one study collected data retrospectively (Edenfield et al, 1995), and one study combined both designs (Wilson & Sill, 1973) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies used a limited study population (Table 2). Seven studies targeted only high-risk pregnant women (e.g., short cervical length, history of PTB, or contractions) (Allouche et al, 2011; Gioan et al, 2018; Goodfellow et al, 2019; Hueston, 1998; Lee et al, 2020; Takagi et al, 2012; Woolery, 1992), and three studies were conducted in specific races (de Caunes et al, 1990; Misra et al, 2001; Weber et al, 2018). Two studies targeted only the black population (de Caunes et al, 1990; Misra et al, 2001), and one study compared non-Hispanic black and white women (Weber et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Applying a fixed threshold to direct prophylactic interventions, as Goodfellow et al. have suggested, undermines QUiPP's value and is not the advised approach . Currently, prophylactic interventions should be directed to those with a short cervix.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%